Opioid and non-opioid analgesic prescribing practices for pediatric adenotonsillectomy in a tertiary care center. (December 2022) - Commesso, Emily A.; Osazuwa-Peters, Nosayaha; Frank-Ito, Dennis O.; Einhorn, Lisa; Ji, Keven S.Y.; Greene, Nathaniel H.; Eapen, Rose J.; Raynor, Eileen M.
Abstract: Importance: The U.S. is in an opioid epidemic with greater than 40, 000 deaths annually. Pediatric adenotonsillectomy is one of the most common and painful otolaryngology surgeries performed, often associated with opioid prescriptions. Objective: To understand postoperative prescribing practices of adenotonsillectomy in a tertiary care institution and associated postoperative emergency department (ED) visits. Design: Descriptive analysis of retrospective cohort data. Setting: Tertiary academic healthcare institution. Participants: Pediatric patients <18yo undergoing adenotonsillectomy between 2013 and 2016. Interventions/exposures: Postoperative analgesic regimens assessed including opioid and non-opioid analgesic prescriptions upon discharge from tonsillectomy surgery. Main outcomes and measures: Main outcomes included ED presentation within 30-days of surgery and reoperation. Secondary outcomes included reason for ED presentation and relation to prescribed analgesics. Data was analyzed between November 2021–February 2022. Results: 200 patients were included in the study with 69% prescribed opioids, and 51% prescribed non-opioid analgesics. Number of opioid doses ranged widely with a median of 37 (Q1, Q3: 0, 62). There were no demographic differences in patients prescribed opioids from those who were not. Of those patients who presented to the ED, 81% were not specifically prescribed acetaminophen (p < 0.001). Regression analysis models were not predictive of postoperative analgesic regimen or 30-day ED presentation (p > 0.05) Conclusions: Wide ranges of post tonsillectomy prescribing practices currently exist in our institution. Prescribing acetaminophen may help to reduce 30-day ED presentation rate. Larger prospective studies are needed to optimize pain control regimens and reduce variability of opioid prescribing practices. Standardization of postoperative pain medication doses may also reduce postoperative ED presentations. Highlights: Opioids are commonly prescribed following pediatric adenotonsillectomy. Wide range of opioids was prescribed at our tertiary care institution. Acetaminophen prescription was associated with a decrease in 30-day ED presentation.